Yvette Duval and the Late Antique North Africa: It is Not Just Decline and Fall Anymore - Nsiri, Mohamed-Arbi (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
Yvette Duval’s publications offer diverse and contrasting aspects about the dynamism of late-antique North Africa. I have underlined the extent to which they were able to exert a considerable influence in recent historiography. The ideas defended in her various articles and books cannot leave anyone indifferent. Discussing them, drawing up a critical assessment, seeing them questioned, does not mean doing an iconoclast’s work. On the contrary, it is the best tribute that can be paid to a wo man who defended the idea of a multicolored Late Antiquity, far from the stereotypes resulting from the Aufklärung of crisis an decadence.
Keywords: french historian; historiography; Late Antique North Africa; Late Antiquity; Later Roman Empire